Konsep Penerapan Syariat Islam dalam Pencegahan Perilaku Menyimpang pada Remaja SMA Kota Banda Aceh - Abubakar Abubakar (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2009)
This article is purposed to know how concept, system and obstacles in implementing Syariah (Islam Law) in preventing misbehaviours on senior high school effectively. The respondences of this research come from related agencies, either Islam Law Department, School, Student Organization. Data collection was done by questionnaires, interview, workshop. The results of concept prevention deviate behaviour on teenages of Senior High School of Banda Aceh are: a) Direct Prevention Concept, Direct Prevention Concept is concept which assumed immediately can prevent misbehaviour of either teenages or the other age; (b) Indirect Prevention Concept, this kind of prevention is planning and sustainable attempts which can be used to prevent also can reduce one or groups intention to do disgraceful actions against values of Syariah (IslamLaw); (c) Guiding Concept, guiding is an effort of Syariah Department in giving and enhancing understanding to teachers and students regarding with True Syariah Implementation, along with sanctions faced as consequences of violationvalues; (d) Violation Prevention through Identification of Place and Violation Forms, and (e) Problems found by Department of Syariah in Preventing Deviate Behaviours Teenages in Senior High School Particularly.